2023
DOI: 10.37990/medr.1345373
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of SARS-COV-2 Infection During Pregnancy on Fetal Doppler Ultrasound Parameters: A Prospective Study

Mehmet ÖZER,
Pınar Tuğçe ÖZER,
Süleyman Cemil OĞLAK
et al.

Abstract: Aim: The fetal effects of severe acute respiratory syndrome coronavirus-2 (SARS-COV-2) infection have been the subject of controversy since the beginning of the pandemic. We aimed to investigate the effect of SARS-COV-2 infection on fetal Doppler parameters. Material and Methods: This prospective case-control study was conducted at Health Sciences University, Izmir Tepecik Education and Research Hospital between September 1, 2021, and June 1, 2022, on pregnant women confirmed to have SARS-CoV-2 by RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Moreover, Mehmet, Ö et al, 23 conducted a prospective case-control study that enrolled 81 pregnant women who had mild to moderate COVID-19 infections during their pregnancy and 70 patients who had no RT-PCR positivity or symptoms during their pregnancy to evaluate the effects of COVID-19 infection on neonatal outcomes in the late preterm period, fetal biometry, and fetal Doppler measurements and revealed that Uterine A, Umbilical A, MCA Doppler measurement (pulsatility index [PI], systolic/ diastolic ratio [S/D]), cerebroplacental ratio (CPR), amnion fluid index, head circumference, abdominal circumference, and femur length measurements performed in the late preterm period between 34 and 37 weeks, and there was no difference significantly between COVID-19 and control groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Mehmet, Ö et al, 23 conducted a prospective case-control study that enrolled 81 pregnant women who had mild to moderate COVID-19 infections during their pregnancy and 70 patients who had no RT-PCR positivity or symptoms during their pregnancy to evaluate the effects of COVID-19 infection on neonatal outcomes in the late preterm period, fetal biometry, and fetal Doppler measurements and revealed that Uterine A, Umbilical A, MCA Doppler measurement (pulsatility index [PI], systolic/ diastolic ratio [S/D]), cerebroplacental ratio (CPR), amnion fluid index, head circumference, abdominal circumference, and femur length measurements performed in the late preterm period between 34 and 37 weeks, and there was no difference significantly between COVID-19 and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Inclusion criteria: Pregnant women who had been infected with SARS-COV-2 infection during early pregnancy (first trimester or early second trimester), Maternal Age: -Range between 22-35 years' old and BMI (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Methodsmentioning
confidence: 99%